DEVELOPMENT OF MATHEMATICS MODULE BASED ON RECIPROCAL TEACHING LEARNING MODEL ON SUB-MATERIAL LINEAR EQUATION AND INEQUALITIES OF ONE VARIABLE - Haristha Rachmawati; Suparman Suparman (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2019)
Lack of mathematical communication and students' learning independence and low creativity become obstacles in achieving educational goals. One of the teaching materials that can help to achieve education goals is a module. These research aims are to develop, test the feasibility and know the student's response to the development of mathematics module based on the learning model of reciprocal teaching on the subject of equations and linear inequality of one variable. The type of research conducted is development research (R&D). The development mathematics module's research subjects are media expert, material expert, and some junior high school students (SMP)Muhammadiyah 1 Godean and State Junior High school (SMPN) 2 Tempel. This research object is the learning module of mathematics based on reciprocal teaching forSMPClassVIIin the sub-material Equations and Linear Inequality One Variable. The data collection techniques are based on interviews in both schools. The research instrument use questionnaires. The data from the research results are analyzed qualitatively and quantitatively. The qualitative data get from interviews, and the quantitative data get from Questionnaires. The research results show that media experts give scores of ratings had an average of 131.5 in excellent criteria; scores by material experts had an average of 133.33 that indicate very well criteria. The result of the student response instrument calculations had an average of 124.12 in very well criteria. Based on the calculation, the mathematics module is developed can be used in learning mathematics.